Польські впливи в руських грамотах XIV-XVII ст. - Геращенко, Ольга М (Slavia Occidentalis, 2024)
This paper aims to analyze the role of Polish documents and the official Polish business language in the formation and development of the syntax and, more generally, the style of Ruthenian deeds from the second half of the 14th and the first half of the 17th century. Since the formula of Ruthenian acts from the 14th to the first half of the 16th century developed under the influence of Czech and Latin models, as well as the then casual or business Polish, by the middle of the 16th century, a certain similarity had emerged between Russian- and Polish-language registers. In fact, the stage was set for the adoption and functioning of subsequent borrowings from the Polish formular, which in such circumstances did not seem artificial or alien in the Russian language. The influence of the formular of the Polish-language deeds became evident in Ruthenian diplomas from the mid- 16th century. Over time, they intensified and reached the peak by the mid- 17th century. Polish influences in the style of Ruthenian deeds following the Union of Lublin manifested themselves in the use of new formulas and in the role of the Polish language as a disseminator and activator of linguistic phenomena corresponding to Polish ones: anything that did not resemble the Polish style models had to be changed to bear the resemblance. On the other hand, it should be stressed that the development of the Ruthenian formular was not a slavish imitation of other stylistic models. Rather, it was a creative process: the formulas were modified to form new variants of linguistic clichés. From the mid- 16th century, especially following the Union of Lublin, the syntax of the Russian acts (heavily influenced by the Polish language) was reconstructed according to the rhetorical model. This was due both to the general rhetoric prevailing in Polish prose genres, and to the spread of the European Latin-language model of education in the Polish-Lithuanian Commonwealth, including Ukraine. Rhetoric at the level of the syntax was reflected in the dominance of the period, based on the hypotactic principle, and was the main characteristic of the syntactic organization of the text.